2013
DOI: 10.1016/j.marpolbul.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Coral recruitment and potential recovery of eutrophied and blast fishing impacted reefs in Spermonde Archipelago, Indonesia

Abstract: a b s t r a c tCoral recruitment was assessed in highly diverse and economically important Spermonde Archipelago, a reef system subjected to land-based sources of siltation/pollution and destructive fishing, over a period of 2 years. Recruitment on settlement tiles reached up to 705 spat m À2 yr À1 and was strongest in the dry season (July-October), except off-shore, where larvae settled earlier. Pocilloporidae dominated nearshore, while a more diverse community of Acroporidae, Poritidae and others settled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
42
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 45 publications
11
42
2
Order By: Relevance
“…Across the full year of study, coral densities were minimal in the Gulf and Musandam (mean: 38 and 30 coral settlers m −2 year −1 , respectively, across the year, and averaging 82 and 70 settlers m −2 year −1 even when considering only the peak settlement season), and corals were entirely absent from settlement tiles in the Sea of Oman throughout the study. The observed densities were substantially lower than has commonly been reported in tropical reef environments (Seychelles: 595 spat m −2 year −1 , ChongSeng et al, 2014;Indonesia: 286-705 m −2 year −1 , Sawall et al, 2013;Kenya: 101-908 m −2 year −1 , Mangubhai et al, 2007), and less than half of densities reported for comparable high latitude marginal reefs (Eilat: 190 m 2 year −1 , Glassom and Chadwick, 2006;Solitary Islands: 132 spat m −2 year −1 , Harriott and Banks, 1995;Taiwan: 111 spat m −2 year −1 , Soong et al, 2003). The observed densities are also low compared with a recent study of coral settlement in Dubai in the southern Gulf where densities of 121 coral settlers m −2 year −1 were reported (Bauman et al, 2014), although those data were mainly collected on breakwaters that have been suggested to entrain eggs, potentially enhancing settlement compared with what would occur on natural reefs (Burt et al, 2009).…”
Section: Coral Settlement Patternsmentioning
confidence: 53%
See 1 more Smart Citation
“…Across the full year of study, coral densities were minimal in the Gulf and Musandam (mean: 38 and 30 coral settlers m −2 year −1 , respectively, across the year, and averaging 82 and 70 settlers m −2 year −1 even when considering only the peak settlement season), and corals were entirely absent from settlement tiles in the Sea of Oman throughout the study. The observed densities were substantially lower than has commonly been reported in tropical reef environments (Seychelles: 595 spat m −2 year −1 , ChongSeng et al, 2014;Indonesia: 286-705 m −2 year −1 , Sawall et al, 2013;Kenya: 101-908 m −2 year −1 , Mangubhai et al, 2007), and less than half of densities reported for comparable high latitude marginal reefs (Eilat: 190 m 2 year −1 , Glassom and Chadwick, 2006;Solitary Islands: 132 spat m −2 year −1 , Harriott and Banks, 1995;Taiwan: 111 spat m −2 year −1 , Soong et al, 2003). The observed densities are also low compared with a recent study of coral settlement in Dubai in the southern Gulf where densities of 121 coral settlers m −2 year −1 were reported (Bauman et al, 2014), although those data were mainly collected on breakwaters that have been suggested to entrain eggs, potentially enhancing settlement compared with what would occur on natural reefs (Burt et al, 2009).…”
Section: Coral Settlement Patternsmentioning
confidence: 53%
“…While many studies have focused efforts on understanding the dynamics of coral settlement following disturbance (Glassom et al, 2004;Abelson et al, 2005;Green and Edmunds, 2011;Sawall et al, 2013;Bauman et al, 2014), few studies have explored the role that non-coral benthos may play in affecting early recovery dynamics on reefs (Colvard and Edmunds, 2011;Luter et al, 2016). Non-coral benthos are among the first colonists to settle on substrates opened by disturbance, and typically reach an abundance and coverage that greatly exceeds that of coral spat (Dunstan and Johnson, 1998;Díaz-Castañeda and Almeda-Jauregui, 1999;Glassom et al, 2004;Mangubhai et al, 2007;Stubler et al, 2016).…”
Section: Coral Settlement Patternsmentioning
confidence: 99%
“…Sampling took place between April and June 2014, between the wet NW monsoon (Dec-Feb) and the dry SE monsoon (June-Sept) in this area (Sawall et al, 2013). Three islands exposed to different levels of anthropogenic impact, due to varying distance from Makassar, were selected for this study.…”
Section: Study Areamentioning
confidence: 99%
“…Several dozen, mostly inhabited small islands fringed by coral reefs provide the unique possibility to study reefs subjected to various natural and anthropogenic influences, mainly related to the city of Makassar with 1.5 million inhabitants (Sawall et al, 2012(Sawall et al, , 2013Polónia et al, 2015), resulting in an environmental gradient with increasing distance from the city (Cleary et al, 2005;Polónia et al, 2015;Teichberg et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation